Parents' Knowledge on Diarrhea in a Plantation Area - Arizal Arizal; Ali Antoni; Sari Leyli Harahap; Atan Baas Sinuhaji; A. H. Sutanto (Paediatrica Indonesiana, 1994)
The parents' knowledge on diarrhea was evaluated by a cross sectional study in Balirnbingan plantation PTP Vlll Kabupaten Simalungunon December 18-19, 1992. The study was conducted by providing questionnaires to 216 parents of infants and children with diarrhea. Most parents (97.2%) knew that diarrhea was a disease, wbile six of them (2.SOA>) thought that diarrhea was not a disease but was associated with the increase level of intelligence or teeth eruption. Seventy-five percent of parents thought that fluid and electrolyte ought to be given to children with diarrhea, and 16.5 % thought to give anti-diarrheal drugs or traditional medicaments. Fluid and electrolytes were given as an initial treatment for diarrhea by most of the parents (69%). Eight per cent of parents gave diarrheal drugs and 12% used traditional medicaments. They got oral electrolyte solution (OES) from the health workers (63.3%) or from the dispensaries or drug stores (36.7%). Most of the parents (53.7%) thought that OES was useful to stop diarrhea. Only 30.3% knew that OES was used as the substitute of fluid loss, 16% thought it was to cure for stomach ache. As many as 57.4% parents knew diarrhea as an infectious disease and 57.4 % knew how to prevent it. Most of them knew that environmental sanitation could prevent the disease (23.3%). Food and beverages were known as vehicle of infections by 37.5% parents.